Challenging Universality: gender portrayals in television commercials in South Africa and Germany - Hoess, Johanna (Centre for Film and Media Studies, 2025)
This study explored gender portrayals in television commercials in South Africa and Germany. Quantitative content analysis is commonly used in cross-cultural advertising research, often relying on codebooks developed in one cultural context and applied universally. Guided by a decolonial perspective, this research aimed to challenge these “methodological universalisms” (Mohanty, 2003) by developing and validating a culturally relevant quantitative instrument. Moreover, this study was the first to compare gender portrayals in television advertising between South Africa and Germany. Adopting a social constructionist viewpoint on gender, the analysis employed Ashmore's (1990) gender domains to examine gender constructions as dynamic and multifaceted phenomena. The research utilised a mixed-methods design, beginning with a qualitative phase followed by a quantitative phase. In the qualitative research phase, a small subsample of 30 South African and 30 German television commercials was analysed using thematic analysis. The qualitative results informed the development of the quantitative codebook during the interim phase of instrument development. This new codebook was then applied to a sample of 459 television commercials in the subsequent research phase, the quantitative content analysis. Key gender related themes from the thematic analysis included demographic characteristics, contexts, roles and activities, advertising-specific aspects, nonverbal expressions, and physical attributes. The final codebook consisted of 15 relevant variables to examine gender constructions in South African and German television commercials. By categorising variables according to Ashmore's (1990) framework within the codebook, the study aimed to capture all relevant aspects of gender as communicated in advertising. As suggested by the results, this context-specific quantitative instrument revealed different outcomes compared to previous research, with German commercials exhibiting more systematically gendered portrayals than South African advertisements. In Germany, nine of the fifteen variables, including product type, setting, age, body type, attire, passive vs. active behaviour, symbolic behaviour, interest, and company, were significant, indicating a focus on specific gender-related expectations, especially for female characters. In South Africa, four variables-product type, age, body type, and relationships status-were significant. The comparative analysis revealed that male characters in German ads tended to be more objectified, while female characters conformed to narrower and more conventional expectations compared to their South African counterparts. Subsequently, findings for select variables (gender, age, relationship status, and race) were contextualised with census statistics, which indicated a notable overrepresentation of young characters in German commercials compared to the population. These findings suggest the need to re-evaluate conventional quantitative codebooks, emphasising the importance of updating measurement tools and critically reviewing their relevance to the specific contexts under analysis.